An Improved Greedy Parameter Stateless Routing In Vehicular Ad Hoc Network - Kavita Kavita; Neera Batra; Rishi Pal Singh (Institute of Advanced Engineering and Science, 2018)
Congestion problem and packet delivery related issues in the vehicular ad hoc network environment is a widely researched problem in recent years. Many network designers utilize various algorithms for the design of ad hoc networks and compare their results with the existing approaches. The design of efficient network protocol is a major challenge in vehicular ad hoc network which utilizes the value of GPS and other parameters associated with the vehicles. In this paper GPSR protocol is improved and compared with the existing GPSR protocol and AODV protocol on the basis of various performance parameters like throughput of the network, delay and packet delivery ratio. The results also validate the performance of the proposed approach.